Developing a common user interface for information searching. - Hollis R; Brunelle BS (Electronic Library, 1995)
This paper reviews the debate over a Common User Interface design across various hardware platforms and operating systems, for both CD-ROM and online searching of bibliographic and full-text databases. The implementation and further development of Z39.50 as an international standard for structured bibliographic data structures is also discussed.